The role of the right valuation method in setting the firm’s break-even price for mpox (and other) vaccines - Peter-Jan Engelen; Danny Cassimon (BMJ Global Health)
Critical voices on unfairly high mpox and other vaccine prices open the debate on the ‘right price’ to be paid to private vaccine suppliers. We apply compound real options analysis as a more appropriate valuation method to derive a correct firm’s break-even price. Real option models are better able to capture the development costs, associated risks and the embedded operational flexibility in vaccine development in a superior way compared with more traditional net present value (NPV) methods. The real option price is lower than standard NPV-based methods, thereby providing a basis to improve the bargaining position of payers in negotiating better vaccine price outcomes. Deeper insights into the correct break-even price will create a more balanced playing field between firms and payers. This can also lead to more equitable access to vaccines in developing countries.